Keanekaragaman Jenis Kupu-Kupu Di Kawasan Hutan Batu Tikar Kecamatan Luwuk Kabupaten Banggai - Anggo, Sulasmi; Karim, Wahyudin Abdul; Samaduri, Alwia; Erni, Nila (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2022)
Abstrack : Butterflies can maintain a balance of biological systems and promote normal varieties in the flower pollination process. Butterflies can also function as pollinators, facilitating the natural reproduction of plant ecosystems. The existence of butterflies in Batu Tikar Forest Area needs attention. This study aims to determine the types of butterflies found in the Batu Tikar Forest Area and determine the variety of butterflies in the Batu Tikar Forest Area. This research was conducted in Batu Tikar Forest Area Luwuk District, Banggai Regency. The sample is a type of butterfly obtained using butterfly net fishing gear at the Research Site. The sampling was carried out by exploring the Batu Tikar Forest Area which had been determined as a place to explore. Then count all the types of butterflies that have been obtained in the Batu Tikar Forest Area, and identify the butterflies that have been obtained during the research. The results concluded that the types of butterflies found at the research site genus were Mycalesis, Mycalesis, Faunis, Cyrestis, Dolescalla, Vindula, Lasippa, Pareronia, Zethera, Ideopsis, Orsotriaena, Eurema, Pithecops, Cepora, Euploea, Lamasia, Papilio, Graphium dan Papilio. With a total of 75 individuals. Variety of Butterfly Species in the Batu Tikar Forest Area, Luwuk District, Banggai Regency, with a value of H'= 2.56, meaning that the variety is moderate.